Time to Breathe: An Investigation of Teachers' Experiences of Mindfulness in the Classroom - Bree, Catherine (My University, 2018)
With the rising presence of mindfulness practices in schools in Ireland, it is important to review and assess the experiences of those implementing the practice. In particular, teachers' understanding of the topic needs to be considered. This research study reports the experience of seven teachers in a school which does not incorporate a particular mindfulness programme or whole school approach to the practice. Findings point to a high level of openness to mindfulness in schools. However, a lack of time to include the practice in the school day was evident, as well as an understanding of mindfulness that in some cases does not align with its fundamental aims. The author concludes that there is a need for mindfulness in schools. It can be particularly beneficial in counteracting the sense of time-deprivation experienced by teachers, and hence teachers should be provided with resources in order to offer a more comprehensive practice to children.
Professional Master of Education
Keywords: Research Subject Categories; Mindfulness; Time-deprivation; Practice